2012
DOI: 10.4269/ajtmh.2012.11-0217
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High Prevalence of Infection of Bithynia siamensis goniomphalos with Opisthorchis viverrini Cercariae in Different Wetlands in Thailand and Lao PDR

Abstract: Abstract. The carcinogenic liver fluke, Opisthorchis viverrini, requires Bithynia snail intermediate hosts in its life cycle. However, the prevalence of O. viverrini in snail intermediate hosts is typically low ( 1%). Here, we examined B. siamensis goniomphalos from 48 localities in Thailand and The Lao People's Democratic Republic (Lao PDR) and reported highprevalence levels of O. viverrini. The highest-prevalence levels per locality were 6.93% (mean = 3.04%) in Thailand and 8.37% (mean = 2.01%) in Lao PDR; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…goniomphalos snail length above 8 mm was considered as mature snails. The cercariae shedding procedures in Kiatsopit et al (2012) were followed to determine the O. viverrini infection rate in B.s. goniomphalos snails, and if mature snails were more susceptible to infection.…”
Section: Snail Samples For Assessing Species Abundance and Diversitymentioning
confidence: 99%
“…goniomphalos snail length above 8 mm was considered as mature snails. The cercariae shedding procedures in Kiatsopit et al (2012) were followed to determine the O. viverrini infection rate in B.s. goniomphalos snails, and if mature snails were more susceptible to infection.…”
Section: Snail Samples For Assessing Species Abundance and Diversitymentioning
confidence: 99%
“…Trematode infection in B. s. goniomphalos was examined by cercarial shedding, 11 where individual snails were placed in small plastic containers (3 cm in diameter and 2.5 cm high) half filled with dechlorinated water (5 mL) and exposed to a 60 W light for 5 hours. The emerged cercariae were identified by morphology according to the keys published by Schell.…”
Section: Methodsmentioning
confidence: 99%
“…in Bithynia snails, particularly in B. s. goniomphalos, is typically low, although it is also variable (0.03-8.37% in infected populations), in contrast to the high prevalence found in fish and human hosts. [6][7][8][9][10][11] In addition to O. viverrini s.l., several groups of trematodes can be found concurrently in B. s. goniomphalos. These often have several fold higher prevalences of infection than for O. viverrini s.l.…”
Section: Introductionmentioning
confidence: 99%
“…This low probability of infection success is counteracted by the large numbers of O. viverrini eggs released into the environment by a single infected host. This finding also sheds some light on the extremely low snail prevalence observed, generally ranging between 0.2% and 1.2% in Thailand (reviewed in Petney et al, 2012, but see Kiatsopit et al, 2012). Understanding why snail prevalence is so low, by means of characterizing the encounter and compatibility filters (Combes, 2005) between snails and eggs will be essential for improving our understanding of transmission dynamics, improving current modeling investigations and further informing environmental control strategies.…”
Section: Discussionmentioning
confidence: 56%
“…Higher average abundances are generally observed between August and December (reviewed in Petney et al, 2012), suggesting the dominant influence of snail abundance in determining the patterns of seasonal transmission risk in our model output. In contrast, a recent study found snail infection prevalence to be highest during the cool dry season (Kiatsopit et al, 2014), although cercariae release can be high throughout the year (Kiatsopit et al, 2012). Human activity in the environment is usually high during the rainy season, as rain-fed rice farming peaks and coincides with increased fecal bacterial contamination and potentially O. viverrini egg presence in natural water reservoirs (Kaewkes et al, 2012).…”
Section: Discussionmentioning
confidence: 90%